The challenges of nursing in humanized care in the operating room: A literature review (Research, Society and Development, 2024)
The research investigates the challenges faced by nursing in promoting humanized care in surgical centers, using a qualitative literature review approach. The central objective of the research is to identify the challenges of nursing in promoting humanized care in surgical centers using the literature review technique with a bibliographic and documentary approach. As a result, it was identified that workload overload and pressure for efficiency can compromise the quality of care offered by the nursing team, leading to fragmentation of care. Additionally, the impact of technology can reduce interpersonal interactions between professionals and patients. Education and training in humanization are crucial to develop communication and empathy skills in healthcare professionals. Cultural and organizational barriers, such as institutional policies focused on operational efficiency at the expense of individualized care, were also identified as obstacles. It is concluded that humanization should be integrated into the nursing philosophy, prioritizing the human dimension over material and technological resources. The relationship between the nursing team, patients, and families should be based on humanization to ensure effective and satisfactory care in the hospital environment, especially in surgical centers.